2019
DOI: 10.3390/nu11030651
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Probiotic Fermented Milk (PFM) and Yogurt Consumption with Bifidobacterium and Lactobacillus Components of the Gut Microbiota in Healthy Adults

Abstract: The current study investigates whether probiotic fermented milk (PFM) and yogurt consumption (YC) are related to both the ingested bacteria taxa and the overall gut microbiota (GM) composition in healthy adults. PFM and YC habits were analyzed in 260 subjects (51% male) by specific questionnaires, and the following groups were considered: (1) PFM groups: nonconsumers (PFM-NC, n = 175) and consumers (PFM, n = 85), divided as follows: Bifidobacterium-containing PFM (Bif-PFM; n = 33), Lactobacillus-containing PFM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 60 publications
4
35
2
Order By: Relevance
“…Growth of Bifidobacterium spp. was minor, but statistically significant as those bacteria inhibit proliferation of pathogens by production of organic acids [42]. Moreover, decrease in a population of C. histolyticum could be observed.…”
Section: The Influence Of Polyphenol Compounds Contained In Tea On Inmentioning
confidence: 89%
“…Growth of Bifidobacterium spp. was minor, but statistically significant as those bacteria inhibit proliferation of pathogens by production of organic acids [42]. Moreover, decrease in a population of C. histolyticum could be observed.…”
Section: The Influence Of Polyphenol Compounds Contained In Tea On Inmentioning
confidence: 89%
“…This is an observational study based on a convenience sub-sample from the ALMICROBHOL study population [ 27 ]. Two hundred and sixty-one adults between 25 and 50 years, and with a BMI between 18.5 and 35 kg/m 2 , participated in the later project.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, B. animalis subsp lactis added to yoghurt products, was found to be increased in the yoghurt consumer group of the TwinsUK cohort. Both bacterial species/subspecies are used in the making of fermented milk products and were found to be increased in the gut of yoghurt consumers in several other observational studies [19,20]. Yet, the B. animalis subsp lactis observation was not replicated in the LifeLines-DEEP cohort, potentially indicating that dairy products consumed by participants of in the LifeLines-DEEP cohort were less enriched in B. animalis subsp lactis.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, Zhernakova et al, found a positive association between the frequency of a speci c fermented milk product consumption and gut microbiota diversity in a population of over 1000 subjects [18]. Furthermore, study of 260 volunteers revealed that those consuming yoghurt presented elevated levels of S. thermophilus in their gut while an increase in Bi dobacterium species was observed in Bi dobacterium-containing fermented milk consumers [19]. Finally, using a targeted approach Suzuki et al described that yoghurt and fermented dairy products consumption in 250 young Japanese adults was associated with increased levels of Lactobacillus and decreased Staphylococcus [20].…”
Section: Introductionmentioning
confidence: 99%